Approaching Other Animals with Caution: Exploring Insights from Aquinas's Psychology - Haan, Daniel D. De (New blackfriars, 2019)
In this essay I explore the resources Thomas Aquinas provides for enquiries concerning the psychological abilities of nonhuman animals. I first look to Aquinas's account of divine, angelic, human, and nonhuman animal naming, to help us articulate the contours of a ‘critical anthropocentrism’ that aims to steer clear of the mistakes of a naïve anthropocentrism and misconceived avowals to entirely eschew anthropocentrism. I then address the need for our critical anthropocentrism both to reject the mental-physical dichotomy endorsed by ‘folk psychology’ and to articulate a more adequate ‘commonsense psychology’ that acknowledges most embodied animal behavior is observable psychological behavior. Next, I argue that we can develop Aquinas's doctrine of estimation and conation to formulate an account of nonhuman animal action that more adequately characterizes the purposeful behaviors of nonhuman animals. To do so, we first need to recognize a wider range of nonhuman animal behaviors that are captured by Aquinas's ‘estimative sense’, and that all of these behaviors are specified by a finite variety of particular goods confined to the animals’ environmental niches. But we also need to supplement Aquinas's account of human and nonhuman animal agency by exploring the ontogeny and ecology of how humans and other animals become attuned to affordances within these different environmental niches. I argue that we should look to Aquinas's account of nonhuman animal capacities in ST I-II 6-17 for subtle insights that can expand our understanding of how nonhuman animals engage in purposeful behavior by exercising analogous nonrational and imperfectly voluntary forms of intention, deliberation, choice, execution, and enjoyment. I conclude with an outline for how future enquiry can seek to explain the nonrational purposeful problem-solving competencies of chimps, canines, corvids, cetaceans, cephalopods, and other nonhuman animal species.